Hubungan Antara Citra Tubuh Dengan Self Esteem Pada Wanita Yang Melakukan Perawatan Di Skin Care - rohmah, Nazilatur; , Dra. Wiwien Dinar P, M.Si (2015)
In the current era, many women who considered that their physical appearance is still less than perfect. Negative assessment conducted on him showed that women have a low self esteem. Low self esteem is generally caused by a negative body image for himself. The purpose of this study is to investigate the relationship between body image self esteem in women who perform treatments in skin care. The hypothesis proposed that there is a positive relationship between body image self esteem in women who perform treatments in skin care. Subjects in this study amounted to 130 people, women aged 18-40 years, who perform maintenance in MM Clinic Aesthetic Skin Center. The sampling technique used in this study is Incedental sampling. Data was analyzed using product moment correlation analysis using the program SPSS 15.0 For Windows program. Based on the calculations, the correlation coefficient r xy = 0.718 with sig = 0.000 (p ≤ 0.01). These results indicate that there is a positive relationship between self-esteem with body image. Effective contribution (SE) body image of the self-esteem of 51.5% shown by the coefficient of determination (r²) of 0.515. The level of self esteem in women who perform treatments in skin care was moderate while the level was moderate body image. Keywords: self-esteem, body image, skin care